2009
DOI: 10.1111/j.1365-2141.2009.07662.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of regulatory T cells in children with autoimmune neutropenia

Abstract: Summary CD4+ 25+ regulatory T cells (Tregs) play a role in controlling the development and progression of autoimmunity. The transcription factors Foxp3 and NFATC2 (NFAT1) play key roles in regulating the development and function of Tregs. The present study examined the involvement of Tregs in the pathophysiology of autoimmune neutropenia in children. Tregs were analysed by flow cytometry, based on the expressions of CD4, CD25, and intracellular Foxp3. The expressions of FOXP3 and NFATC2 mRNA in the CD4+ 25+ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
5
13
0
Order By: Relevance
“…In this paper, our data showed that there was a significant decrease in the frequencies of Treg cells in peripheral blood of DCM patients by flow cytometry based on their characteristic CD4 + CD25 + membrane phenotype, but the percentage of CD4 + T cells in PBMCs was similar between DCM patients and normal controls, in accordance with the result of a study showing that the percentage of suppressor/cytotoxic T cells was low in idiopathic dilated cardiomyopathy compared with healthy controls and ischaemic heart disease 31. However, the frequency and number of Treg cells have been described as normal, low or high in other autoimmune diseases,17 18 29 32 so we conclude that many uncontrollable factors may result in the discrepant results. First, different autoimmune diseases maybe have different alteration of Treg cells in human peripheral blood.…”
Section: Discussionsupporting
confidence: 77%
“…In this paper, our data showed that there was a significant decrease in the frequencies of Treg cells in peripheral blood of DCM patients by flow cytometry based on their characteristic CD4 + CD25 + membrane phenotype, but the percentage of CD4 + T cells in PBMCs was similar between DCM patients and normal controls, in accordance with the result of a study showing that the percentage of suppressor/cytotoxic T cells was low in idiopathic dilated cardiomyopathy compared with healthy controls and ischaemic heart disease 31. However, the frequency and number of Treg cells have been described as normal, low or high in other autoimmune diseases,17 18 29 32 so we conclude that many uncontrollable factors may result in the discrepant results. First, different autoimmune diseases maybe have different alteration of Treg cells in human peripheral blood.…”
Section: Discussionsupporting
confidence: 77%
“…1b (4·49 ± 0·99% versus 5·87 ± 1·44% and 0·78 ± 0·17% versus 1·00 ± 0·33%; P = 0·0123 and P = 0·0123, respectively). This result was partly consistent with those reported in our previous study [9]. The low frequency of total T regs may be caused by the decrease in activated T regs that play an important role in suppressive function to avoid autoantibody production in autoimmune disease (including AIN).…”
Section: Resultssupporting
confidence: 93%
“…Several researchers have attributed causes of this disease to the modification of antigens after exposure to drugs, molecular mimicry of microbial antigens, post‐infectious autoantibodies and differences in human leukocyte antigen types [5–8]. Previously, we reported a deficiency of regulatory T cells [T regs ; CD4 + CD25 + forkhead box protein 3 (FoxP3) + T cells] in children with AIN as another cause of this disease [9]. T regs play a key role in suppressing the immune response based on the control of autoimmunity in peripheral tissue [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis is that the suppressor system in these infants is immature and that the spontaneous recovery corresponds with the full development of suppressor T‐cell function (1) at about 3 yr of age. Recently, Nakamura (10) showed that the frequencies of CD25‐high CD4 T cells and of Foxp3 + CD4 T cells were significantly decreased in AIN infants compared to age‐matched healthy controls.…”
Section: Resultsmentioning
confidence: 99%